KETERSEDIAAN UNSUR HARA SEBAGAI INDIKATOR PERTUMBUHAN TANAMAN MENTIMUN (Cucumis Sativus L.) - Cristin Lidia Tampinongkol; Zetly ., Tamod; Bertje ., Sumayku (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the availability of nutrients in wet and dry land, and to determine the interaction of the use of soil type and type of fertilizer on the growth of cucumber plants. This research was carried out in Tombatu Tiga Village, District, North Tombatu, Southeast Minahasa Regency for 3 months starting from February - May 2021, using a quantitative descriptive method for nutrient availability and experiments in polybags were carried out using a 4x3 Randomized Block Design (RAK) with 2 factors. treatment, namely Type of Soil and Type of Fertilizer. showed that the availability of macronutrients available in the soil prior to conducting the research (C-Organic, Total N, available P, and K) was less available as well as the pH of the soil on the criteria of slightly acidic to acidic. And from the results of the analysis after the study showed that with the application of organic fertilizer master Compost and POC Nasa there was an increase in soil pH in all soil types, as well as an increase in the value of nutrients, especially available P, followed by C-Organic, and Total N. The results showed that the interaction of soil type and fertilizer type had a significant effect on the growth of cucumber plants at plant heights of 20 DAP and 30 DAP and number of leaves 10 DAP to 30 DAP. However, there was no interaction with plant height at 10 days after planting.